Determinants of Demand for Health Insurance in Uganda: An Analysis of Utilisation and Willingness to Pay - Mpuuga, Dablin; Yawe, Bruno L.; Muwanga, James (Tanzanian Economic Review, 2020)
Health insurance is increasingly being recognized in Uganda as an effective way of protecting people against catastrophic health expenditures. However, only 5 percent of Ugandans hold health insurance, and only 42 percent would consider joining any health insurance scheme. It is in this regard that this study sought to examine the determinants of demand for health insurance in Uganda. After applying a logistic model on Uganda National Household Survey (UNHS) data of 2016/17, the results reveal that awareness is a very crucial factor in determining demand for health insurance, and that most Ugandans are not aware of health insurance as a mode of paying for medical care. The results further reveal that although most of the people suffering from non-communicable diseases are willing to pay for health insurance, very few have health insurance in this regard. Generally, willingness to pay does not translate into actual utilisation of health insurance. Thus, the study recommends the promotion of awareness about health insurance, increasing the literacy levels of Ugandans through education, promoting poverty reduction and income enhancing programs, as well as urgently implementing a National Health Insurance Scheme (NHIS).
Keywords: Demand; Logit; Health insurance